Potential of leguminous tree species to restore the degraded soil - MEVADA, R.J.; PAMPANIYA, NIRAV; BALAS, DUDA B.; PATEL, D.P.; VIYOL, S.V.; NAYAK, DILESWAR; DESHMUKH, H.K.; SURVE, NILAM (Journal of Soil and Water Conservation, 2026)
The essential basic resource needed to satisfy the wide range of human needs is natural resources where one of the most vital resources for human survival is soil. It is among the biotic elements that are essential to maintaining an ecosystem’s food security. A significant determinant of agricultural productivity is soil. Today, in areas where civilization is growing, the soil has all but died. In India, over 30% of the land is degraded. The symbiotic relationship between Arbuscular mycorrhizal fungi and nodulating N‚ -fixing bacteria allows leguminous tree species to recover the deteriorated soil. From the present discussion, information generated that soil was improved under legume tree species by increasing the OC and available N, P, and K and also by reducing the bulk density of soil. Moreover, it has a better capacity to grow quickly and withstand degraded land; thus, leguminous tree species have the potential to establish and grow in degraded land and improve soil health through the nitrogen fixation nature and organic matter more than non-leguminous tree species. From the literature, several researchers have reported that leguminous tree species are one of the best alternatives for the reclamation of soil. Leguminous trees, i.e., Prosopis juliflora, Dalbergia sisoo, Glyricidia sepium, Leucaena leucocephala, Albizia lebbeck, Prosopis cineraria, Pithecellobium macradenium, etc., are important tree species for reclaiming the soil health by adding organic matter in soil from the leaf litter and fixing nitrogen. These leguminous tree species not only improved soil health but also have multipurpose use, which helps the grower to generate income.